2017
DOI: 10.21149/8141
|View full text |Cite
|
Sign up to set email alerts
|

Association of dengue fever with Aedes spp. abundance and climatological effects

Abstract: Objective. To analyze the association of dengue fever incidence with Aedes mosquito's abundance, and the effect of climatological and geographical variables, in a region in Morelos State, Mexico. Materials and methods. Weekly data during the period 2010 to 2014 was used. Mosquito abundance was determined using ovitraps. Confirmed dengue cases were obtained from the Epidemiological Surveillance System. Climatic variables were obtained from weather monitoring stations. The correlation between climate variables a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 14 publications
1
15
0
1
Order By: Relevance
“…Hence, we anticipate the GOS traps to be able to bring down dengue cases, by trapping (infected) gravid Aedes mosquitoes. Although some studies collectively indicate only a 22% positive correlation between vector indices and dengue cases [53], other studies found significant correlation between weekly Aedes abundance (in egg counts and ovitrap index) with number of confirmed dengue cases [53, 54]. Increase in Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we anticipate the GOS traps to be able to bring down dengue cases, by trapping (infected) gravid Aedes mosquitoes. Although some studies collectively indicate only a 22% positive correlation between vector indices and dengue cases [53], other studies found significant correlation between weekly Aedes abundance (in egg counts and ovitrap index) with number of confirmed dengue cases [53, 54]. Increase in Ae.…”
Section: Discussionmentioning
confidence: 99%
“…However, OPI has been shown to be a good proxy for adult indices [29, 33, 58], so we believe our approach is both appropriate and useful. Finally, this paper aimed to provide a broad characterisation of vector patterns and does not consider seasonality, an important component of vector and dengue transmission dynamics [3, 8, 28, 29, 32, 40, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Similar definitions have been used to study dengue incidence in Belo Horizonte [8, 40]. The eight‐week difference was chosen as a conservative estimate of the temporal lag between egg indices and dengue incidence [41, 42]. This definition aligned the beginning of the study year with the annual nadir, or lowest value, of each variable and allowed us to capture the entire seasonal curve in a single year.…”
Section: Methodsmentioning
confidence: 99%
“…To analyze mosquito density, we used the Human Hour Bite Index (HHBI), which is a useful entomological indicator to estimate the presence and abundance of populations of adult insect vectors 73 . The HHBI calculates the number of mosquitoes feeding on a person per hour, using the following formula: HHBI=total mosquitoes capturednumber of collection hours0.50em×0.50emnumber of collectors These records were made over 13 days distributed over five observation months: June, July, September, October and November, which include the months of highest rainfall in Cuernavaca and coincide with the maximum emergence of adult mosquitoes 74 …”
Section: Methodsmentioning
confidence: 99%